Magnetic mountain : Stalinism as a civilization - Kotkin, Stephen (University of California Press, 1997)
This study is the first of its kind: a street-level inside account of what Stalinism meant to the masses of ordinary people who lived it. Stephen Kotkin was the first American in 45 years to be allowed into Magnitogorsk, a city built in response to Stalin's decision to transform the predominantly agricultural nation into a "country of metal." With unique access to previously untapped archives and interviews, Kotkin forges a vivid and compelling account of the impact of industrialization on a single urban community. Kotkin argues that Stalinism offered itself as an opportunity for enlightenment